Automatic Threshold on Current based Anti-pinch Mechanism for Power Windows - Wahyu Kunto Wibowo; Seok-Kwon Jeong; Sam-Sang You; Lee Jaemin (Institute of Advanced Engineering and Science, 2018)
In this paper, the automotive power window has been integrated with an advanced safety mechanism called anti-pinch system for good protection. Based on a contact method, a new safety mechanism using a low-cost technology has been proposed to set a threshold value as a limit to decide the pinch condition, or automatic threshold method. The electric current information is easily detected by using current sensor installed on a motor driver without incorporating extra device. Then the pinch condition is quickly reflected and calculated by using current information in the system. Since the automatic threshold is decided by analyzing system behavior in advance, the optimal calculation can be guaranteed and then applied it on the safety mechanism in a cost-effective manner. Through extensive experimental tests, the squeezing forces of the proposed anti-pinch system have been verified to satisfy requirements of the FMVSS 118 regulations.